(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Describe the nutritional status and eating habits of Y1 and Y3 medical students at Hanoi Medical University in the 2022-2023 academic year. Methods: Cross-sectional descriptive study on 520 Y1 (n = 260) and Y3 (n = 260) students. Data were collected through direct interviews and anthropometric measurements. Body mass index (BMI) was classified according to WHO 2007 standards (for Y1) and WHO 2000 (for Y3). Results: The malnutrition rate in Y1 students was 5%, the rate of chronic energy deficiency (CED) in Y3 students was 19.6%. The rate of overweight-obesity (TC_BP) in the two groups was 7.3% (Y1), 6.6% (Y3), respectively. Only 16.9% of the study subjects ate three main meals, 32.5% hardly ate breakfast. The rate of skipping breakfast in women (36.6%) was higher than that of men (29.1%). Male students consumed meat more often than females (p<0.05), while females tended to eat less protein-rich foods. Conclusions: The rate of CED in medical students is still significant, especially in Y3 students. Eating three main meals, especially breakfast, is important in improving nutritional status. It is necessary to implement nutrition education programs in schools, develop reasonable menus in the cafeteria and support students to raise awareness of healthy diets.